InCell VR: A Virtual Reality-based Application on Human Cell Division for Mobile Learning - Nasharuddin, Nurul Amelina; Khalid, Nur Atasha; Hussin, Masnida (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Many teaching and learning tools incorporate current technologies for the learners to gain new knowledge thus increasing the efficiency of learning. Some of the technologies adopted in the mobile-based education systems are virtual reality, augmented reality, and mixed reality. In the Biology field, one of the problems faced by the learners is the difficulties in visualizing the human cell division process in the topic of mitosis and meiosis. Thus, many innovations which adopt these technologies are created to improve the understanding and interest of the learners. In this work, an interactive mobile learning application with virtual reality technology has been designed and developed to help learners visualize the human cell division process. The mobile application which is known as InCell VR also includes mini games which can help to test and improve the learners’ understanding. The InCell VR was developed using Unity, a game engine platform for developing high performance commercial game. The final evaluation assesses two parts: the learners’ knowledge gain after using the application and usability evaluation of the application. The usage of the proposed application was seen to give positive impact on the development of learners’ knowledge from the pre- and post-test testing sessions. The usability study showed that InCell VR application is useful, easy to be used and learnt, and give satisfactions to the users.